O comportamento da política fiscal brasileira no período pós-Plano Real e suas implicações - Andreis, Augusto Alberto (Universidade do Vale do Rio dos Sinos, 2016)
The main objective of this dissertation was to analyze the fiscal policy’s behavior in post Plano Real implementation period. Knowing that public finances are directly affected by the economic cycle, the analysis were made through the methodology of structural budget balance, which has as its basic premise the cyclically component of revenue and expenditure elimination. That being, it has been chosen to compute the structural budget balance by the optic of OECD and IMF, being that, in the last case, it has been utilized two distinct methods to obtain elasticity of revenue with respect to output. The results indicate that, between 1998 and 2015, the fiscal policy conduction can be divided into three distinct periods. The first of them, which comprehends the period 1998-2003, the fiscal policy had as objective to generate primary balance, that is, this period can be considered a moment of fiscal adjust, considering that there has been recurrent fiscal contractions, however, this fiscal policy orientation has made that to submit a procyclical behavior towards it self. The second period, which comprehends the 2004 to 2011 period, can be considered where the fiscal policy has been utilized as a tool for smoothing the wavy movements of economy, that is, it can be affirmed that the fiscal policy had an countercyclical behavior. And finally, the third period, which comprehends the period between 2012 to 2015, where has been recurrent fiscal expansions, and can be considered a moment when the fiscal policy has been used to expand the aggregate demand, what ended up to making its behavior to be procyclical. It is important to point out that the fiscal adjustment that occurred between 1998 and 2003, which has reduced the federal public debt considerably, can be one of the factors that allowed utilizing fiscal policy as an anticyclic tool during the subprime crisis. In that way, the importance of a new fiscal adjustment to confront possible future crisis is put in perspective. Besides that, the fiscal adjustment period in Brazil should had occurred between 2012 and 2014, a moment where the GDP grown above its long term tendency, but the moment was lost. In that way, the importance of a new fiscal adjustment to confront possible future crisis is put in perspective. Besides that, the fiscal adjustment period in Brazil should had occurred between 2012 and 2014, a moment where the GDP grown above its long term tendency, but the moment was lost. In that manner, expansionist fiscal policy has contributed towards the country’s growth above its trend and also to the worsen of public finances for a few years. The fiscal adjustment proposal pretended in 2016 becomes too expensive than if it was done before. Furthermore, the brazilian fiscal policy presents too little similarities with its neighbour countries and none of them presented fiscal expansion similar to Brazil’s between the years of 2012 and 2015. Although, comparing Brazil’s fiscal behavior with countries in BRICS, too liitle similarities are found once again.
Keywords: Política fiscal; Ciclo econômico; Balanço orçamentário estrutural; Fiscal policy; Business cycle; Structural budget balance; ACCNPQ::Ciências Sociais Aplicadas::Economia